1984
DOI: 10.1128/jb.157.1.53-58.1984
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of genes involved in the biosynthesis of pseudobactin, a high-affinity iron transport agent of a plant growth-promoting Pseudomonas strain

Abstract: A gene bank of DNA from plant growth-promoting Pseudomonas sp. strain B10 was constructed using the broad host-range conjugative cosmid pLAFR1. The recombinant cosmids contained insert DNA averaging 21.5 kilobase pairs in length. Nonfluorescent mutants of Pseudomonas sp. strain B10 were obtained by mutagenesis with N-methyl-N'-nitro-N-nitrosoguanidine, ethyl methanesulfonate, or UV light and were defective in the biosynthesis of its yellow-green, fluorescent siderophore (microbial iron transport agent) pseudob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

1984
1984
2002
2002

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(24 citation statements)
references
References 34 publications
(32 reference statements)
1
22
0
Order By: Relevance
“…This fits well with the situation in Pseudomonas sp. strain B10, where minimally 12 genes in four separate clusters are needed for the biosynthesis of pseudobactin (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This fits well with the situation in Pseudomonas sp. strain B10, where minimally 12 genes in four separate clusters are needed for the biosynthesis of pseudobactin (22).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, complementation studies with nonfluorescent mutants, defective in siderophore biosynthesis, of Pseudomonas sp. strain B10 have indicated that a minimum of 12 genes arranged in four gene clusters is required for the biosynthesis of pseudobactin (22).…”
mentioning
confidence: 99%
“…All recombinant DNA procedures have been described elsewhere [17]. Cosmids carrying di¡erent Pseudomonas B10 genomic fragments [19] were transferred from E. coli HB101 to P. aeruginosa by triparental matings with pRK2013 [20]. Exconjugants were selected on SM9 and screened for £uorescent emission under UV light exposure.…”
Section: Manipulation Of Nucleic Acids and Genetic Techniquesmentioning
confidence: 99%
“…This observation indicates that PvdS is required for PpsbA transcription in the heterologous P. aeruginosa host, and suggests that a pvdS homolog is present in Pseudomonas B10. To search for this gene, eight cosmids encompassing the pseudobactin region of the Pseudomonas B10 genome [19] were individually screened for their ability to complement the pvdS mutation P. aeruginosa PAO OT11pvdS [8]. Cosmid pJLM4A, containing a DNA insert of 26.8 kb, was able to restore the £uorescent phenotype in PAO OT11pvdS.…”
Section: Identi¢cation Of the Psbs Genementioning
confidence: 99%
“…Eight pLAFR1-derived cosmids from a genomic library of Pseudomonas strain B10 (25) were individually screened for the ability to complement the pvdA mutation in the nonfluorescent, L-Orn N 5 -hydroxylase-deficient Pseudomonas aeruginosa mutant PALS124 (pvdA). Only pJLM1, carrying a DNA insert of approximately 23 kb (25), was able to restore the fluorescent phenotype in PALS124 grown on KB agar plates (13). Subcloning in the shuttle vector pUCP18 and deletion analysis localized the complementing DNA region within the 2.7-kb PstI-SphI insert of pCA⌬Sh.…”
mentioning
confidence: 99%